Immigration - Martin, Claudia (Our world in crisis, 2018)
Comprehensive explorations of major issues affecting the global community. People have many different reasons for leaving their home country, but they are nearly always looking for a better or safer life. This book considers the pull factors that attract people to another country and the push factors that drive them from their home country. It looks at movements of people in the past, the impact of current immigration and the arguments that people put forward in favour or against welcoming immigrants to a country. It asks readers to think about what they can do to learn more about this global issue and the people affected by it